2021
DOI: 10.1007/s00024-021-02860-6
|View full text |Cite
|
Sign up to set email alerts
|

Warming in Europe: Recent Trends in Annual and Seasonal temperatures

Abstract: Contemporary climate warming is a key problem faced not only by scientists, but also all by humanity because, as is shown by the experience of recent years, it has multiple environmental, economic and biometeorological implications. In this paper, the authors identify the magnitude of annual and seasonal temperature changes in Europe and its immediate surroundings on the basis of data from 210 weather stations from 1951 to 2020. An analysis of temperatures in the 70-year period shows that air temperature has c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 45 publications
6
33
0
1
Order By: Relevance
“…DJF trends remained statistically non-significant, and for MAM, only an increase in the maximum temperature was statistically significant. This is in clear agreement with advanced global warming (e.g., [5][6][7][8]) and temperature increases observed everywhere in Europe (e.g., [11,40,[42][43][44][45]). Despite the changes in the character of the distribution (density curves, percentiles, skewness, kurtosis), these growing trends were not reflected in significant increases in temperature variability as expressed by the standard deviation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…DJF trends remained statistically non-significant, and for MAM, only an increase in the maximum temperature was statistically significant. This is in clear agreement with advanced global warming (e.g., [5][6][7][8]) and temperature increases observed everywhere in Europe (e.g., [11,40,[42][43][44][45]). Despite the changes in the character of the distribution (density curves, percentiles, skewness, kurtosis), these growing trends were not reflected in significant increases in temperature variability as expressed by the standard deviation.…”
Section: Discussionsupporting
confidence: 85%
“…We are trying to document this by carrying out a comparison of both 30-year climate normals for the homogenised annual and seasonal series of several climatic variables calculated for the territory of the Czech Republic during the 1961-2020 period. As Twardosz et al [8] showed in their analysis of 210 stations in Europe, the air temperature has continued to grow linearly since 1985, i.e., seems to be less influenced by recent global warming than 1991-2020. Despite the fact that the previous studies in the Czech Republic dealt with incomplete 60-year periods (for example, Brázdil et al [9] with wind speed, Brázdil et al [10] with precipitation or Zahradníček et al [11] with temperatures), the last study by Zahradníček et al [12], which dealt with temperature extremes during the entire 60-year period 1961-2020, clearly demonstrates significant differences between both 30-year normal sub-periods.…”
Section: Introductionmentioning
confidence: 97%
“…An increase in the variability of precipitation has been observed in recent decades, which have been exceptionally warm. For example, 2010 was a year of heavy precipitation and disastrous floods in central Europe [7], and 2018 saw a long period of hot and dry weather in many areas of the continent [8][9][10]. Obviously, there are a number of determinants behind precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, accurate intense rainfall forecasts and risk communication are important to mitigate these natural hazards' socioeconomic impacts. The Mediterranean region, as a climate change hotspot, especially for the greatest warming in summer [3], is frequently struck by severe rainfall events causing lots of casualties and several million euros of damage every year [4]. In this region, the unusually complex terrain, surrounding the western Mediterranean sea, characterized by steep coastal mountains (Alps, Apennines, Massif Central, Pyrenees), often enhances or triggers deep convective processes originating over the warm sea in the fall season [5][6][7].…”
Section: Introductionmentioning
confidence: 99%